Time-Frequency Analysis of FSK Digital Modulation Signals using the Smooth Lag-Windowed Wigner-Ville Distribution. - Sha'ameri, Ahmad Zuri (2003)
Digital modulation signals such as FSK are time-varying signals that can he represented in the time-frequency representation. The smooth lag-windowed Wigner-Ville distribution (SLWWVD) is proposed as a method to obtain accurate time-frequency representation of FSK signals used in HF (High Frequency) radio communications. Unlike existing time-frequency distributions such as the windowed Wigner-Ville distribution (WWVD) or the smooth windowed Wigner- Ville distributioii (SWWVD). the proposed timefrequency distribution does not require priori knowledge of the signal modulation parameters such as the hitduration and subcarrier frequencies. The algorithm generates the time-frequency representation directly based on the signal characteristics. Comparison based on mainlobe width and signal-to-interference ratio shows the SLWWVD generate accurate time-hquency representation for simulated and actual communication signals.